Self-compassion links premenstrual symptom severity to social and emotional well-being in nursing students - Güzin Ünlü Suvari; Merve Coşkun (Scientific Reports, 2026)
Abstract Premenstrual syndrome (PMS) is associated with impaired quality of life in women. Although self-compassion has been associated with psychological well-being, its role in the relationship between premenstrual symptom severity and PMS-specific quality of life (PMS-QoL) remains unclear. This study investigated the mediating role of self-compassion among nursing students. In this cross-sectional study, 164 nursing students with Premenstrual Syndrome Scale (PMSS) scores ≥ 110 completed the Self-Compassion Scale and the Premenstrual Syndrome–Specific Quality of Life Scale (PMS-QoL). Pearson’s correlation and mediation analyses were conducted using PROCESS Model 4 with 5,000 bootstrap samples, adjusting for age, body mass index, and menstrual pain intensity. Greater premenstrual symptom severity was associated with lower self-compassion ( r = − 0.263, p < 0.01) and poorer PMS-QoL ( r = − 0.367, p < 0.01), whereas self-compassion exhibited a positive association with PMS-QoL ( r = 0.353, p < 0.01). Self-compassion partially mediated the association between premenstrual symptom severity and overall PMS-QoL (indirect effect = − 0.045, 95% bootstrap CI: −0.085 to − 0.015), as well as the social and emotional well-being domains, but not the physical well-being domain. These findings highlight the potential of self-compassion as a psychological resource for improving PMS-specific quality of life and fostering health and well-being among university nursing students.